Fashion companies and customer satisfaction: A relation mediated by Information and Communication Technologies. (July 2018) - Amendola, Carlo; Calabrese, Mario; Caputo, Francesco; Fabrizio, D'Ascenzo
Abstract: Adopting the interpretative lens provided by the Systems Thinking and Service Logic, the paper pursues a twofold aim: 1] from one side it offers a wider picture of fashion sector with the aim to support both researchers and practitioners in defining more valuable and effective approaches and 2] from the other side it investigates the customers' perspectives and their approach to Information and Communication Technologies in the fashion sector. After the definition of four hypotheses, the perceptions of a sample of 1125 customers are investigated through a qualitative survey and the results are analysed using Structural Equation Modelling.